PERSEPSI PEMUDA DAN PEMUDI TERHADAP PEKERJAAN DI SEKTOR PERTANIAN DAN NON PERTANIAN DI KABUPATEN LAMPUNG SELATAN - Viantimala, Begem; Gultom, Dame Trully (Indonesian Journal of Socio Economics)
The objectives of the research were to study (1) The perception of youth generation on the agriculture and non agriculture job (2) The contribution of youth generation income taken from agriculture job  and non agriculture  on the household income (3) The factors related to the youth perception in agriculture and non agriculture job. The research was conducted using survey metod in Tanjung Bintang Sub District central, South Lampung District.  The samples were 140 peoples.  They were proportionately randomly selected with 10% precision from 417 peoples population.  The data collected were analyzed descriptively and statistically using Rank Spearman correlation.  The study showed that (1)  The perception of youth generation in agriculture job are not good enough in economically, phisicaly and prestige.  The perception of youth generation in non agriculture job are economically and prestige good  but phisicaly not good enough.  (2) Contribution of youth generation income  taken from non agriculture job biger than agriculture job.  (3) There was correlation between socialization and  the youth perception in non agriculture job.